Pollen, XRF, biomarkers, charcoal of the COL17c record, Colônia Basin, São Paulo-Brazil - Rodríguez-Zorro, Paula A; Ledru, Marie-Pierre; Favier, Charly; Bard, Edouard; Bicudo, Denise C; García, Marta; Marquardt, Gisele; Rostek, Frauke; Sawakuchi, André Oliveira; Simon, Quentin; Tachikawa, Kazuyo (PANGAEA, 2022)
The COL17c composite record was analyzed based on pollen, charcoal, the elemental composition of bulk sediment obtained by X-Ray fluorescence scanning (XRF) and biomarkers (branched glycerol dialkyl glycerol tetraethers (brGDGTs), n-Alkanes and Hopanes). We aimed to characterize early states of the Atlantic forest to evaluate the link with southern hemisphere climate variability at orbital scales using a sediment core located at the transition between SASM (South american summer monsoon) and subtropical front influence.
Keywords: Araucaria; Atlantic forest; Brazil; early Pleistocene; Southern Hemisphere; Subtropical Front